Erosive osteoarthritis - Ongkowijaya, Jeffrey A; Setiyohadi, Bambang; Sumariyono, Sumariyono (Indonesian Rheumatology Association, 2010)
Osteoarthritis (OA) is a degenerative joint disease characterized by the erosion of cartilage joints, hypertrophy of the marginal bone, subchondral sclerosis, and the morphological and biochemical changes of synovial membrane and joint capsule.This clinical syndrome is characterized by joint pain caused by degeneration of the joints. It is the most common joint disease to afflict the elderly and it occurs more often with age.1â3 Erosive osteoarthritis is a subset of OA in which there is a destruction of the joints as a result of inflammation.3,4 Changes mainly occur on the distal interphalangeal (DIP) joints, proximal interphalangeal (PIP) joints, carpometacarpal (CMC) joints, and very rarely occur on other joints of hand or of other body parts.3â5 The diagnosis is in accordance with the criteria of American College of Rheumatology (ACR) for OA and is supported by the existence of bone erosion on the radiological image. The management of this disease is merely for palliative purpose.